Association between diabetes mellitus and hepatic encephalopathy in patients with cirrhosis. Issue 3 (29th June 2020) - Labenz, Christian; Nagel, Michael; Kremer, Wolfgang M.; Hilscher, Max; Schilling, Caroline A.; Toenges, Gerrit; Kuchen, Robert; Schattenberg, Jörn M.; Galle, Peter R.; Wörns, Marcus‐Alexander
Summary: Background: Diabetes mellitus may lead to increased serum ammonia and systemic inflammation thereby promoting hepatic encephalopathy (HE). Aim: To investigate the potential association between diabetes mellitus/glycaemic control and the presence of covert HE as well as the development of overt HE in a prospective setting. Methods: A total of 240 patients with liver cirrhosis were included into this prospective cohort study and followed for a median of 17 months. Covert HE was diagnosed by pathological results in the Portosystemic Hepatic Encephalopathy Score. Predictors for the presence of covert HE or the development of overt HE were analysed using logistic regression or Cox‐regression models. Results: At study inclusion, 65 patients (27.1%) presented with diabetes mellitus and covert HE was detected in 33.3%. Patients with diabetes mellitus had a more preserved liver function as compared to patients without diabetes mellitus (MELD 9 vs 10; P = 0.043). In regression analyses after adjustment for confounders, diabetes mellitus was independently associated with the presence of covert HE at study inclusion and the development of overt HE during follow‐up. These associations were confirmed in separate propensity‐score‐weighted regression models. In subgroup analyses, patients with worse glycaemic control (HbA1c >= 6.5%) had a pronounced risk for covert HE (OR 2.264, 95% CI 1.002‐5.118) and overt HE (HR 4.116, 95% CI 1.791‐9.459). Conclusions: Diabetes mellitus may associate with higher risk for the presence of covert HE and the development of overt HE in patients with liver cirrhosis. Adequate glycaemic control may be a potential target to attenuate this important complication.